Interplay of health-related quality of life and comorbidities in people with type 2 diabetes mellitus treated in primary care settings in Austria: a countrywide cross-sectional study - Faisal Aziz; Martin Clodi; Michael Resl; Julia K Mader; Harald Kojzar; Susanne Kaser; Harald Sourij; Peter Fasching; Norbert Joachim Tripolt; Kehkishan Azhar; Caren Sourij; Bernhard Ludvik; et al. (BMJ Open)
Objectives This study assessed the health-related quality of life (HRQoL) and its relationship with clinical factors and comorbidities in people with type 2 diabetes mellitus (T2DM) treated in primary care settings.Design Cross-sectional study design: This study assessed the HRQoL using a 36-item Short Form Survey (SF-36) tool in eight domains. The HRQoL scores ranged from 0% to 100% for each domain, with higher scores indicating better HRQoL. Linear regression was used to assess the association of HRQoL domain scores with clinical covariates and comorbidities.Setting A countrywide study was conducted on individuals with established T2DM (N=635) attending primary healthcare services for various conditions across nine federal states of Austria from 2021 to 2023.Participants A total of 635 individuals, aged above 50 years and diagnosed with T2DM, were recruited by the attending physician to evaluate their HRQoL in relation to T2DM and its associated comorbidities.Results The mean SF-36 scores for physical functioning (69±28), role-physical (62±42), mental health (72±20), role-emotional (73±41), social functioning (79±25), bodily pain (67±28) and vitality (55±22) were satisfactory, except for general health (41±10). Age and body mass were inversely associated with physical, mental and social HRQoL (p<0.05). Women had lower mental health (β: −5.44 [95% CI −9.43 to −1.44], p<0.05) than men. Smokers and those with cardiovascular and chronic lung diseases reported worse general, mental and physical health and vitality (p<0.05 each). Depression (p<0.001) and multimorbidity (p<0.05) severely deteriorated all HRQoL domains: physical functioning (Depression:−25.34 [95% CI −33.84 to −16.84], p<0.001); (Multimorbidity: −19.37 [95% CI −26.30 to −12.44], p<0.001), physical role limitations (−22.96 [95% CI −36.65 to −9.27], p<0.001); (−18.53 [95% CI −29.59 to −7.48], p<0.001), social functioning (−24.38 [95% CI −32.41 to −16.35], p<0.001); (−8.86 [95% CI −15.66 to −2.07], p<0.05), emotional well-being (−19.80 [95% CI −26.22 to −13.38], p<0.001); (−9.54 [95% CI −14.95 to −4.13], p<0.001), emotional role limitations (−28.26 [95% CI −41.01 to −15.52], p<0.001); (−8.15 [95% CI −18.78 to 2.49], p=0.133), bodily pains (−23.09 [95% CI −32.21 to −13.97], p<0.001); (−14.52 [95% CI −22.08 to −6.95], p<0.001), fatigue (−16.47 [95% CI −23.40 to −9.55], p<0.001); (−13.71 [95% CI −19.39 to −8.03], p<0.001), general health (−7.09 [95% CI −10.40 to −3.78], p<0.001); (−7.14 [95% CI −9.83 to −4.46], p<0.001).Conclusions Our analysis showed that advanced age, obesity, depression, cardiovascular disease, chronic lung diseases and multimorbidity were associated with poor HRQoL of individuals with T2DM at the primary care level. These findings highlight the need for strengthening holistic management in primary care to address the diverse physical, social and emotional needs of individuals with T2DM.